1994
DOI: 10.1007/bf00199684
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reorganization of microtubules and microfilaments in flax cells during the resistance response to flax rust infection

Abstract: Abstract. The cytoskeleton in plant cells is a dynamic structure that can rapidly respond to extracellular stimuli. Alteration of the organization of microtubules and actin microfilaments was examined in mesophyll cells of flax, Linum usitatissimum L., during attempted infection by the flax rust fungus, MeIampsora lini (Ehrenb.) Lev. Flax leaves that had been inoculated with either a compatible (yielding a susceptible reaction) or an incompatible (yielding a resistant reaction) strain of M. lini were embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 55 publications
4
108
0
1
Order By: Relevance
“…41 Later stages of HR are often accompanied by depolymerisation of F-actin. 42,43 Microtubule organisation is also affected by defence responses, but the response is variable. Disruption and apparent depolymerisation of the microtubule network at the penetration site has been observed in several systems (Figure 1n), 39,40,44 and it has been suggested that this might be an early sign of the HR.…”
Section: Involvement Of the Cytoskeleton In The Hypersensitive Responmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Later stages of HR are often accompanied by depolymerisation of F-actin. 42,43 Microtubule organisation is also affected by defence responses, but the response is variable. Disruption and apparent depolymerisation of the microtubule network at the penetration site has been observed in several systems (Figure 1n), 39,40,44 and it has been suggested that this might be an early sign of the HR.…”
Section: Involvement Of the Cytoskeleton In The Hypersensitive Responmentioning
confidence: 99%
“…Disruption and apparent depolymerisation of the microtubule network at the penetration site has been observed in several systems (Figure 1n), 39,40,44 and it has been suggested that this might be an early sign of the HR. 39,42 In other studies microtubules, like F-actin, concentrate at the infection site and undergo bundling, 42 but some studies 43 found no changes in the microtubule organisation upon pathogen attack. Treatment with cryptogein induces depolymerisation of microtubules 41,45 providing further support of the idea that microtubules are involved in HR.…”
Section: Involvement Of the Cytoskeleton In The Hypersensitive Responmentioning
confidence: 99%
“…This is well established from a number of Zinnia studies (see 31 and references therein), based on cortical microtubule rearrangement associated with cell isolation. In the hypersensitive response, links between microtubule and microfilament organization and cell death have been identified (32,33).…”
Section: Microtubule Rearrangementmentioning
confidence: 99%
“…Interactions between fungi and plant species and using different methods of tissue prepcells also result in changes in the arrays of MTs in aration did not support this finding, plant cells. For example, various biotrophic fungal Mycorrhizal fungal associations with orchids are pathogens cause varying degrees of cortical MT of particular interest because of their essential role in depolymerization in plant cells during infection peg seed germination and protocorm development and or haustorium formation ; their similarity in many respects to biotrophic fungal Gross et al, 1993;Kobayashi, Kobayashi & infections. In most orchid species, fungal hyphae Hardham, 1994). Microtubules are absent from host invade the very reduced embryo and form hyphal cell cytoplasm contiguous to the haustorium coils called pelotons, which are separated from the branches, which are surrounded by host cell mem-host cytoplasm by an interfacial matrix and host brane.…”
Section: Introductionmentioning
confidence: 99%